Penerapan Sistem Pakar Diagnosa Penyakit Autisme pada Anak dengan Metode Forward Chaining Berbasis Web - Ariska, Fera; Yulianton, Heribertus (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Autism is a developmental problem in children that affects behavior, language, social interaction, and learning skills. One of the causes of autism is a serious neurobiological problem that affects the ability of the mind so that children are unable to connect and communicate with the outside world effectively. However, some parents do not know the early signs and symptoms of this autism disorder, so early detection is neglected. Autism usually appears before a child reaches the age of three. The increasing number of people with autism is caused by a lack of awareness or understanding of parents about this condition. The purpose of making this expert system is to make it easier for parents or the general public to learn various kinds of autism behavior, the symptoms it causes, and the treatment options needed for children with autism. The rules used in this system refer to the criteria for autistic disorders contained in DSM IV. The method used in this expert system is Forward Chaining. Forward Chaining is used to test the factors entered with the rules stored in the system until conclusions can be drawn. The results of the validation test were 83.3% and proved that the system functionality was functioning properly. This application has also been tested directly on experts and patients diagnosed with autism, and the output results are the same as the experts' diagnoses.